Medication Interruptions and Subsequent Disease Flares During the COVID‐19 Pandemic: A Longitudinal Online Study of Patients With Rheumatic Disease. Issue 5 (8th March 2022) - Dharia, Tiffany; Venkatachalam, Shilpa; Baker, Joshua F.; Banerjee, Shubhasree; Curtis, David; Danila, Maria I.; Gavigan, Kelly; Gordon, Jennifer; Merkel, Peter A.; Shaw, Dianne G.; Young, Kalen; Curtis, Jeffrey R.; et al.
Abstract : Objective: We aimed to assess trends in anxiety and interruptions in disease‐modifying antirheumatic drug (DMARD) use among patients with rheumatic diseases during the COVID‐19 pandemic and to evaluate whether DMARD interruptions were associated with disease flares. Methods: ArthritisPower, the Vasculitis Patient‐Powered Research Network, and other patient organizations invited members to join a 52‐week longitudinal study, with baseline surveys completed March 29 to June 30, 2020, with follow‐up through May 2021. Logistic regression incorporating generalized estimating equations evaluated associations between interruptions in DMARD use and self‐reported disease flares at the next survey, adjusting for demographic characteristics, medications, disease, and calendar time. Results: Among 2, 424 patients completing a median of 5 follow‐up surveys, the mean age was 57 years, 87% were female, and the most common conditions were rheumatoid arthritis, vasculitis, and psoriatic arthritis. Average Patient‐Reported Outcomes Measurement Information System (PROMIS) anxiety T scores decreased from April 2020 (58.7) to May 2021 (53.7) ( P < 0.001 for trend). Interruptions in DMARD use decreased from April (11.2%) to December 2020 (7.5%) ( P < 0.001) but increased through May 2021 (14.0%) ( P < 0.001). Interruptions in DMARD use were associated with a significant increase in severe flares (rated ≥6 of 10) at the next survey (12.9% versus 8.0% [odds ratio (OR) 1.71 (95% confidence interval [95% CI 1.23, 2.36]) although not any flare (OR 1.18 [95% CI 0.89, 1.58])]. Conclusion: Anxiety and interruptions in DMARD use initially decreased over time, but DMARD interruptions increased during 2021, possibly related to an increase in COVID‐19 cases or vaccine availability. Interruptions in DMARD use were associated with increased rates of severe disease flares, highlighting the importance of avoiding unnecessary DMARD interruptions.